A technique for the determination of the available oxygen in living carp (Cyprinus carpio) muscle - Lucchiari, P. H.; Feofiloff, Edith Fanta; Boscardim, Ana T.; Bacila, M. (Elsevier, 1984)
1. 1. A polarographic method for the measurement of the available oxygen in the muscle of living carp by the use of a platinum microelectrode is proposed. 2. 2. The oxygen and the reference electrodes were assembled in a single insertion piece which was implanted in the muscle of a living carp maintained in a special experimental chamber. 3. 3. Curves for normal oxygen levels corresponding to air-saturated water, as well as to a carbogene-saturated water, were obtained. 4. 4. The method can be considered adequate for the measurement of tissue oxygen in living fishes. © 1984.
Keywords: Carbon dioxide; Fresh water; Sodium chloride; Animal; Carp; Cypriniformes; Electrode; Metabolism; Muscle; Oxygen consumption; pH; Polarography; Temperature; Animal; Carbon Dioxide; Carps; Cyprinidae; Electrodes, Implanted; Fresh Water; Hydrogen-Ion Concentration; Muscles; Oxygen Consumption; Polarography; Sodium Chloride; Support, Non-U.S. Gov't; Temperature